2019
DOI: 10.1016/j.aquaculture.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Partial dietary fish meal replacement with cotton seed meal and supplementation with exogenous protease alters growth, feed performance, hematological indices and associated gene expression markers (GH, IGF-I) for Nile tilapia, Oreochromis niloticus

Abstract: Partial dietary fish meal replacement with cotton seed meal and supplementation with exogenous protease alters growth, feed performance, haematological indices and associated gene expression markers (GH, IGF-I) for Nile tilapia, Oreochromis niloticus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 65 publications
10
48
0
1
Order By: Relevance
“…Omar, Merrifield, Peter, Williams, and Davies () reported very good results for yeast Protein Concentrate (YPC) for carp and noted the high BV (Biological Value) of the protein in these products from bioethanol production from cereals. Furthermore, yeast cells are also potent sources of nucleic acids, mannan oligosaccharides (MOS) and β‐glucans that can be used as immune stimulants and growth promoters in fish diets (Hassaan et al, ; Hassaan, Mahmoud et al, ; Øverland et al, ). Also, It has been reported that live Saccharomyces cerevisiae yeast can settle in the intestinal mucosa of rainbow trout (Øverland et al, ) which may have some effect on the fish larval development (i.e., by quickening the maturation of the digestive system, and having prebiotic and probiotic effects).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Omar, Merrifield, Peter, Williams, and Davies () reported very good results for yeast Protein Concentrate (YPC) for carp and noted the high BV (Biological Value) of the protein in these products from bioethanol production from cereals. Furthermore, yeast cells are also potent sources of nucleic acids, mannan oligosaccharides (MOS) and β‐glucans that can be used as immune stimulants and growth promoters in fish diets (Hassaan et al, ; Hassaan, Mahmoud et al, ; Øverland et al, ). Also, It has been reported that live Saccharomyces cerevisiae yeast can settle in the intestinal mucosa of rainbow trout (Øverland et al, ) which may have some effect on the fish larval development (i.e., by quickening the maturation of the digestive system, and having prebiotic and probiotic effects).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, yeast cells are also potent sources of nucleic acids, mannan oligosaccharides (MOS) and β-glucans that can be used as immune stimulants and growth promoters in fish diets (Hassaan et al, 2019;Hassaan, Mahmoud et al, 2018;Øverland et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Improving the bioeconomic efficiency of aquaculture industry is dependent on advances in biology, nutrition and environmental management of the production cycle (Hassaan et al, ; Hassaan Mahmoud et al, ; Hassaan & Soltan, ). Antibiotics and other veterinary drugs are administered regularly as additives, therapeutics or growth promoters and immunostimulant in fish feed (Rico et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…With an ever‐increasing volume of aquaculture activities around the globe comes growing pressure to maximize the efficiency of finfish production whilst at the same time ensuring sustainability. Typically, being the main expenditure in intensive finfish aquaculture, feeds must be formulated to promote fish performance, maintain the health of fish and be economically viable; they must also increasingly conform to the emerging paradigm of extending beyond satisfying basic nutritional requirements (Hassaan et al, , ; Li & Gatlin, ; Meng et al, ). However, modern aquaculture continues to face an array of nutritional restrictions which threaten optimal culture.…”
Section: Introductionmentioning
confidence: 99%